Transforming Mechanics Education through Innovative Digital Problem-Based Learning: A Bibliometric Analysis - Pratiwi, Safina Ridka; Koranto, Dwi; Lintangesukmanjaya, Rahmatta Thoriq; Sukarni, Sukarni; Khansa, Indri Hapsari; Bergsma, Lindsay Natalia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The digital transformation in education has driven increased attention to the application of problem-based learning (PBL) in technology-based mechanics learning. However, thematic developments, knowledge structures, and research directions in this field have not been systematically mapped. This study aims to analyze publication trends, knowledge network structures, and the development of research topics related to PBL in digital mechanics learning using a bibliometric approach. The research data consists of 189 documents indexed in the Scopus database for the period 2015–2025. Analysis of publication trends, geographic distribution, and relationships between keywords was conducted using VOSviewer software. The analysis results show an increase in the number of publications over the past decade, with contributions concentrated in several countries. Keyword mapping shows the relationship between PBL and topics such as e-learning, game-based learning, and terms related to computing technology such as machine learning and deep learning. Furthermore, temporal visualizations indicate changes in the trend of term usage over time. However, these findings are descriptive and reflect patterns in the analyzed literature, and therefore do not directly indicate a causal relationship or the level of conceptual integration between PBL and digital technology. This research provides a contribution in the form of bibliometric mapping which can be the basis for further research to examine the implementation and integration of PBL in digital-based mechanics learning in more depth.